The Effect of Funding and Liquidity Policy on Investment Decisions with Profitability as Moderating Variables in the Hotel and Tourism Sub Sector Companies - Nanik Nofelina; Diansyah Diansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to determine the effect of funding and liquidity policies on investment decisions with profitability as a moderating variable in hotel and tourism sub-sector companies. The independent variable consists of funding and liquidity policies, and the dependent variable is funding decisions and profitability as a moderating variable. The total population in this study were 35 companies listed on the Indonesia Stock Exchange for the period 2015 – 2019. The sampling method used purposive sampling with a sample of 11 companies according to certain criteria. The data analysis method uses multiple linear regression with calculations using the SPSS program. The results show that funding and liquidity policies have a positive and significant effect on investment policy, while profitability has a positive and insignificant effect on investment decisions. Furthermore, the results of the study of the moderating variable of profitability weakened and insignificant from the influence of funding policy on investment policy as well as the moderating variable of profitability also weakened and insignificant from the influence of liquidity on investment decisions.